Edukasi Gerakan Suhirman Dan Pembagian Tempat Sampah Di Kelurahan Sukapada Kota Bandung - Fuad Hasan; Raden Herdian Bayu Ash Siddiq; Wildan Erdiansyah; Dendi Darmawan; Yura Auliya Hafizha (Jurnal Kabar Masyarakat, 2023)
The benefits of rivers for humans are numerous. Starting from being a source of livelihood, to preventing floods. Caring and maintaining the condition of river is our responsibility. A damaged river will have a bad impact on the environment. A clean river can make the atmosphere of the nearby residential environment more cool. Then the benefit of river for humans is that it can become a recreational place. To achieve this goal, it is necessary to educate the community. UTama Civil Engineering in this case carries out Community Service activities entitled Education of the SUHIRMAN Movement and the Distribution of Painting Waste Bins in Kelurahan Sukapada, Bandung City. The activities carried out at this PKM are socialization regarding the benefits of rivers, how to use them for survival and achieving sustainable development goals and also distributing painting trash bins for local residents.